2010
DOI: 10.2478/v10133-010-0065-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of the Archaeal Diversity in Vlasa Hot Spring, Bulgaria, by using 16S rRNA and Glycoside Hydrolase Family 4 Genes

Abstract: Biodiversity in the archaeal community from Vlasa hot spring, Velingrad, Bulgaria was investigated by sequence analysis of PCR amplified fragments of 16S rDNA and a metabolic gene of glycoside hydrolase 4 family (GH4). The 16S rRNA gene analysis demonstrated that the spring was inhabited predominantly by Crenarchaeota affiliated to two orders, Desulfurococcales (families Pyrodictiaceae and Desulfurococcaceae) and Thermoproteales. Almost half of the 16S rDNA clones were affiliated with hyperthermophilic anaerob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…From a hot spring in Bulgaria, the phylogeny of the archaeal community was analyzed using 16S RNA genes and genes of the glycoside hydrolase-4 family. The good correspondence between both affiliation assignment methods proved the usefulness of these gene encoding metabolic enzymes for phylogenetic studies in heterotrophic archaea [ 11 ]. The study also allowed the direct cloning of these genes of industrial interest [ 11 ].…”
Section: Bacteria and Archaeamentioning
confidence: 99%
“…From a hot spring in Bulgaria, the phylogeny of the archaeal community was analyzed using 16S RNA genes and genes of the glycoside hydrolase-4 family. The good correspondence between both affiliation assignment methods proved the usefulness of these gene encoding metabolic enzymes for phylogenetic studies in heterotrophic archaea [ 11 ]. The study also allowed the direct cloning of these genes of industrial interest [ 11 ].…”
Section: Bacteria and Archaeamentioning
confidence: 99%
“…Molecular phylogeny increasingly supports our understanding of the microbial relationships in the environment and provides the basis for the conventional identification techniques [21]. Comparative sequence analysis based on 16S rRNA is currently the most widely used approach for the reconstruction of microbial phylogeny [10].…”
Section: S Rrna Phylogenetic Analysismentioning
confidence: 99%
“…Among various culture-independent tools, the direct amplification of the 16S rRNA genes from environmental samples using the polymerase chain reaction (PCR) is a commonly employed technique used to describe the composition of complex microbial communities and to gain a descriptive overview of possible differences among communities [8]. In particular, 16S rRNA clone library construction has previously been used to investigate the microbial diversity of sediment environments such as Antarctic continental shelf sediments [9], the Vlasa hot spring of Bulgaria [10], the northern south China sea [11] and a tropical upwelling system [12]. These studies have provided much information on the microbial communities that inhabit sediments and their large bacterial diversity.…”
Section: Introductionmentioning
confidence: 99%
“…our recent studies demonstrated that hot springs in Bulgaria are inhabited by thermophilic microbial communities of rich biodiversity, suitable as a source for sequence-based cloning of novel genes encoding thermostabile proteins, (2,11,26). During our research on sequence-based metagenomic cloning of new genes from glycosyl hydrolase families Gh13 and Gh57 retrieved from hot spring DnA samples and their following expression in B. megaterium, we encountered several problems related to the needs of multiple cloning in expression vectors, as well as, multiple gene fusion cloning and characterization of the enzyme activity and thermal stability of the expressed recombinant proteins.…”
Section: Introductionmentioning
confidence: 99%